Development of an Apparatus for Testing of High-Temperature Static Seals. Issue 3 (4th May 2021) - Sheikhansari, Abdolkarim; Knapton, Jonathan; Benito, Diego; Shaw, Ben; Alborzi, Ehsan; Blakey, Simon
Abstract: A test apparatus is described that evaluates the performance of static aviation seals under an environment similar to the lubrication system in gas turbine engines. The seals can be tested at operating temperatures as high as 400 °C in a static seal rig (SSR). Incorporating an air–oil mist generating system, the test facility exposes the seals to degraded oil, which can deteriorate the performance of seals through chemical attack. The test rig provides representative operating conditions to test four piston and four face seals at the same time. Throughout the aging process of seals, the rig carries out pressure decay leak tests at regular intervals and monitors temperature and pressure at several locations in the test chamber. The capabilities of the rig are demonstrated by presenting the results of durability testing with five types of seals. The results obtained with both successful and failed seals indicate that regular leak testing along with real-time measurement of temperature at the outlet of the low-pressure cavity can provide adequate information as to the operating status of the seals at different stages of testing and operating conditions.